2011
DOI: 10.1098/rspb.2011.1439
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-dependence brings molecular phylogenies closer to agreement with the fossil record

Abstract: The branching times of molecular phylogenies allow us to infer speciation and extinction dynamics even when fossils are absent. Troublingly, phylogenetic approaches usually return estimates of zero extinction, conflicting with fossil evidence. Phylogenies and fossils do agree, however, that there are often limits to diversity. Here, we present a general approach to evaluate the likelihood of a phylogeny under a model that accommodates diversity-dependence and extinction. We find, by likelihood maximization, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
459
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(475 citation statements)
references
References 45 publications
15
459
0
1
Order By: Relevance
“…1 we obtain an exponential growth of infected population. For species phylogenies as well as virus phylogenies, recent methods allow for a saturation effect, meaning the initial exponential growth of the tree is decelerated by having a limited number of ecological niches (macroevolution [33,34]) or a limited number of susceptible hosts (epidemiology [23]). It remains a future challenge to combine the type-dependent models with saturation effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 we obtain an exponential growth of infected population. For species phylogenies as well as virus phylogenies, recent methods allow for a saturation effect, meaning the initial exponential growth of the tree is decelerated by having a limited number of ecological niches (macroevolution [33,34]) or a limited number of susceptible hosts (epidemiology [23]). It remains a future challenge to combine the type-dependent models with saturation effects.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of ecological limits and how they function at higher taxonomic levels have been questioned [24,74,75], yet several studies have demonstrated DD within younger groups, where taxa are well sampled [17,42,73]. For more ancient groups, ecological limits have been detected using phylogenetic methods but here the impact of increasing extinction over speciation may confound interpretation [6,76,77].…”
Section: Discussion (A) Speciation and Extinction Ratesmentioning
confidence: 99%
“…The 12 standard models account for Yule and birth-death processes, as well as changes in speciation rate owing to DD or external factors (SPVAR, Yule 2) such as the environment (monotonic or hyperbolic decay) and changes in extinction rate (EXVAR) or both speciation and extinction (BOTHVAR; [41]). Because none of these models can account for the impact of extinction on DD, we determined l and m values from the Pp tree for each group using the TreePar package in R [25], which uses a maximum likelihood (ML) method to test for constant species diversification, diversity dependence without extinction (DD 2 E) and diversity dependence with extinction (DD þ E), where l and m were taken from the ML estimates [42]. We also reparametrized l and m for the DD þ E analyses to account for extinction when m ¼ 10-50% of the initial l rate.…”
Section: Methodsmentioning
confidence: 99%
“…Declining net diversification results from changes in speciation and/or extinction rate that may reflect diversity-dependent processes such as niche-filling [4,63]. To test whether changes in lineage accumulation are driven by decreasing speciation or increasing extinction, I compared the fits of three time-varying speciation and extinction models (SPVAR, EXVAR and BOTHVAR; [1]) using the second-order Akaike information criterion (AIC c ), which corrects for small sample sizes by penalizing complex models more heavily than the AIC.…”
Section: (C) Tempo Of Lineage and Morphological Diversificationmentioning
confidence: 99%